Exploring research on ecotechnology through artificial intelligence and bibliometric maps - Ricardo Ruiz-Sánchez; Ricardo Arencibia-Jorge; Julia Tagüeña; José Luis Jiménez-Andrade; Humberto Carrillo-Calvet (Environmental Science and Ecotechnology, 2024)
Ecotechnology, quintessential for crafting sustainable socio-environmental strategies, remains tantalizingly uncharted. Our analysis, steered by the nuances of machine learning and augmented by bibliometric insights, delineates the expansive terrain of this domain, elucidates pivotal research themes and conundrums, and discerns the vanguard nations in this field. Furthermore, we deftly connect our discoveries to the United Nations' 2030 Sustainable Development Goals, thereby accentuating the profound societal ramifications of ecotechnology.